CD4+ T Cell Priming as Biomarker to Study Immune Response to Preventive Vaccines - Ciabattini, Annalisa; Pettini, Elena; Medaglini, Donata (Frontiers in Immunology, 2013)
T-cell priming is a critical event in the initiation of the immune response to vaccination since it deeply influences both the magnitude and the quality of the immune response induced. CD4+ T-cell priming, required for the induction of high-affinity antibodies and immune memory, represents a key target for improving and modulating vaccine immunogenicity. A major challenge in the study of in vivo T-cell priming is due to the low frequency of antigen-specific T cells. This review discusses the current knowledge on antigen-specific CD4+ T-cell priming in the context of vaccination, as well as the most advanced tools for the characterization of the in vivo T-cell priming and the opportunities offered by the application of systems biology.